Assessment of mastitic infection in bovine milk using ATP bioluminescence - M. J. Meyer; D. Sukup; Karen A. Schmidt; John E. Shirley (Kansas Agricultural Experiment Station Research Reports, 1998)
Few choices exist for a mobile, rapid, and nonsubjective assessment of mastitic infection in bovine milk. This project evaluated the effectiveness of using the Biotrace® raw milk quality ATP bioluminescence assay to serve this role. Milk samples with various somatic cell counts (13,000 - 2,500,000) and signs of mastitic infection were obtained from the Kansas State University Dairy Teaching and Research Center. Within 24 hr, raw milk samples were evaluated for microbial numbers and relative light units (RLU). The printed test procedure was modified to evaluate accurately clinical mastitic milk samples. As somatic cell count increased in raw milk, the RLU value increased. In addition, RLU values differentiated among milk samples with various levels of mastitic infection (none, subclinical, and clinical). Repeatability of the ATP bio-luminescence method was very good (CV = 4.76%). These results suggest that the Biotrace® raw milk quality test kit can served effectively as a nonsubjective, rapid assay to determine the degree of mastitic infection in bovine milk.; Dairy Day, 1998, Kansas State University, Manhattan, KS, 1998;
Keywords: Dairy Day; 1998; Kansas Agricultural Experiment Station contribution; no. 99-158-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 821; Mastitis; Somatic cell count; ATP bioluminescence